Bond markets in Latin America : on the verge of a big bang? - Borensztein, Eduardo (MIT Press, 2008)
Developing local bond markets is high on the policy agenda of Latin America. This book's case studies of Argentina, Brazil Chile, Columbia, Mexico and Uruguay, written by country experts follow a common methodology, with each offering a history of that country's bond market development and data sets.